A new HPLC–MS/MS method for investigating degradation kinetics of 6‴-feruloylspinosin and identifying its metabolites by rat intestinal bacterial flora in vitro. Issue 15 (13th September 2016) - Song, Panpan; Zhang, Yanqing; Qiao, Longdong; Liu, Junjun; Xie, Junbo; Zhang, Kunsheng; Zhou, Aimin; Wen, Zhiyou
ABSTRACT: 6‴-Feruloylspinosin, a C-glycoside flavonoid, is the active ingredient responsible for the anxiolytic and sedative effects of Zizyphi Spinosiae Semen. However, the degradation mechanism of 6‴-feruloylspinosin in vivo is largely unknown. In this study, we developed a simple and rapid method for determining the degradation of 6‴-feruloylspinosinin in the bacterial culture using high-performance liquid chromatography (HPLC)–tandem mass spectrometry (MS). The precisions were less than 2.93%, and the accuracy (RE%) ranged from −4.07 to 3.09%. The HPLC–MS/MS method was successfully applied to study the degradation kinetics of 6‴-feruloylspinosin and identify its metabolic derivatives. The results indicated that the degradation kinetics and the rate constants were correlated with the concentration of sample solutions and the degradation process could be classified as apparent first-order kinetic reaction. Obviously, the degradation rate of 6‴-feruloylspinosin was rather rapid as 80% of the compound could be decomposed in only 8–12 hr. Furthermore, two metabolites were identified from the serial hydrolysis of 6‴-feruloylspinosin. GRAPHICAL ABSTRACT: